Learning and IT Platforms in Postgraduate Programs, EVA: A proposal for learning - Díaz Zelada, Yvan (2020)
The use of Information Technology in higher education and especially in postgraduate programs and specializations, has implied a series of significant changes in the teaching-learning process, within these changes the creation of the so-called “Virtual Environments” can be highlighted of Learning” or EVA, which give the possibility of breaking the barriers of space and time that exist in traditional education and allow an open interaction to the dynamics of the educational world. This article seeks to analyze whether VAS is a methodology that adds value to students, teachers and educational institutions.